ANALISIS KOHESI GRAMATIKAL DAN KOHESI LEKSIKAL PADA CERPEN DVADTSAT’ DEVYATOE IYUNYA KARYA ANTON CHEKHOV - Nur Barkati, Laila; Purnama Dewi, Anggraeni (Fakultas Ilmu Budaya, Universitas Padjadjaran, 2025)
This research is entitled Analysis of Grammatical and Lexical Cohesion in the Short Story Dvadtsat’ Devyatoe Iyunya by Anton Chekhov. The aim of this study is to identify and analyze the forms of grammatical and lexical cohesion in the short story, as well as to explain their role in constructing the coherence and unity of discourse meaning. The method used is descriptive analysis, which involves describing and analyzing the data in depth based on linguistic phenomena found in the text. The research data were taken from the Russian-language short story by Anton Chekhov entitled Двадцать девятое июня /dvadtsat’ devyatoe iyunya/ ‘Twenty-Ninth of June’ published in Sputnik magazine, Moscow, in 1882. The results of the study show that the grammatical cohesion found includes 4 references of the endophora type, 1 exophora reference, 2 nominal substitutions, 1 verbal ellipsis, and 2 clause ellipses, 3 coordinating conjunctions, and 5 subordinating conjunctions. The lexical cohesion found includes 8 repetitions, 1 synonymy, 4 antonyms, 2 collocations, 1 hyponymy, and 2 metonymies. Keywords: Discourse, Literature, Short Story, Grammatical Cohesion, Lexical Cohesion.